Doin' the twist: new tools for an old concept of myocardial function. Issue 8 (14th July 2008) - Burns, A T; McDonald, I G; Thomas, J D; MacIsaac, A; Prior, D
Abstract : It has been known for some time that the heart rotates during the cardiac cycle in concert with radial and longitudinal motion. With advances in imaging technology, it has been appreciated that the apex and base of the heart rotate in different directions, resulting in a twisting or torsional motion. A new echocardiographic technique, "speckle tracking imaging", permits accurate quantification of this motion. Torsion as well as the timing and magnitude of the rate of torsion (torsional velocity) may provide important new insights into cardiac physiology and disease.